Effect of age on lipid peroxidation of fresh and frozen-thawed semen of Nili-Ravi buffalo bulls. Issue 3 (3rd July 2018) - Ahmed, Sohail; Khan, Muhammad Irfan-ur-Rehman; Ahmad, Mushtaq; Iqbal, Sajid
Abstract: Buffalo bull spermatozoa are rich in polyunsaturated fatty acids and are prone to lipid peroxidation. We hypothesised that lipid peroxidation in buffalo bull semen will increase with age and will affect the semen quality. The objective was to compare malondialdehyde (MDA) concentration and the quality of fresh and frozen-thawed semen between aged (13.6 ± 1.0 years; n  = 3) and young (3.4 ± 0.3 years; n  = 3) Nili-Ravi bulls. The concentration of MDA did not differ ( p >.05) between aged vs. young bulls in fresh (2.3 ± 0.2 vs. 2.9 ± 0.7 nmol mL −1 ), frozen-thawed (53.1 ± 2.8 vs. 48.4 ± 2.6 nmol mL −1 ) semen and seminal plasma (5.71 ± 0.97 vs. 5.19 ± 1.36 nmol mL −1 ), respectively. In fresh semen, sperm motility and total concentration did not differ ( p  > .05) between aged and young bulls. The volume of fresh semen increased ( p  > .05) while sperm viability and DNA integrity decreased ( p  < .05) in aged vs. young bulls. In frozen-thawed semen, sperm motility, viability and DNA integrity decreased ( p  < .05) in aged vs. young bulls. In frozen-thawed vs. fresh semen, MDA level increased within young (48.4 ± 2.6 vs. 2.3 ± 0.2 nmol mL −1 ) and aged bulls (53.1 ± 2.8 vs. 2.9 ± 0.7 nmol mL −1 ). Conversely, sperm motility and viability decreased ( p  < .05) within the age groups between fresh and frozen-thawed semen. In conclusion, (1) lipid peroxidation (MDA) does not increase due to age; however, it is negatively associated with semen quality and (2) cryopreservation steps up lipid peroxidation irrespective of age and deteriorates semen quality of Nili-Ravi bulls.